Belarus : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
In pursuing their economic policy, the authorities have taken advantage of the existence of excess industrial capacity and have relied on price and exchange controls in an attempt to contain inflation pressures. In spite of strong financial support, agriculture performed poorly during 1998, as a result of inclement weather conditions, lack of financial incentives to producers, and aging harvesting equipment. Industrial production expanded at an annual rate of 10 percent, and investment, at a rate of 51/2 percent.